Improvement of solenoid magnetic field and its influence on therapeutic effect during magnetic hyperthermia. (26th May 2020) - Tang, Yundong; Jin, Tao; Flesch, Rodolfo C C; Gao, Yueming
Abstract: Magnetic fields have been widely used in the application of bioengineering, and are expected to distribute as uniformly as possible in order to achieve more effective treatment. The solenoid coil is one of the most popular devices used for producing magnetic fields. However it has proved difficult to achieve a uniform profile in a limited length with this approach. This paper proposes an optimization method to improve the uniformity of the magnetic field for a solenoid coil by considering two correcting coils, which are optimized by using a simulated annealing algorithm for its characteristic parameters. The results after the optimization will further be considered in order to analyse the therapeutic effect on a proposed bio-tissue model during magnetic hyperthermia. The magnetic field distribution inside the solenoid is obtained using Maxwell's theory, and the treatment temperature of the tumor model is determined using Pennes' bio-heat transfer equation. Simulation results demonstrate that the uniformity of the magnetic field can be significantly improved using the proposed method, and that when considering this optimization, the treatment temperature profile presents a better result compared with a single solenoid.